Formulation and evaluation of melt-in-mouth tablets of haloperidol - Jha, Sajal Kumar; P, Vijayalakshmi; Karki, Roopa; Goli, Divakar (Asian Journal of Pharmaceutics (AJP), 2014)
Haloperidol, a butyrophenone, is widely used neuroleptic.Though haloperidol is well absorbed after oral dosing, there is a first pass metabolism leading to a reduced bioavailability of the drug (60-70%).Therefore, the present investigation is concerned with the development of melt-in-mouth tablets of haloperidol.Various formulations were prepared incorporating a combination of superdisintegrants, croscarmellose sodium, sodium starch glycolate, and crospovidone by direct compression method.The formulated melt-in-mouth tablets were evaluated for various physicochemical parameters, disintegration time and for in vitro drug release. All the formulations had disintegration time less than 30 s and release maximum amount of drug by 12 min. Formulation containing higher concentration of crospovidone decreases disintegration time and optimize the drug release. The most satisfactory formulation was found to be stable during the stability studies conducted as per ICH guidelines QIC, as it showed no significant changes (P<0.05) in the physicochemical properties, disintegration time and in vitro drug release.